Faktor-Faktor Pendorong Pertumbuhan Ekonomi Berkualitas di Indonesia - Dikky, Dikky Nur Hidayat; Ayus Ahmad Yusuf; Achmad Otong Busthomi (Jurnal Ekonomi STIEP, 2024)
Quality economic growth is an important aspect of a country's development. Quality economic growth reflects progress that is sustainable, sustainable, and has a positive impact on people's welfare. This study was conducted to determine how influential quality economic growth is through independent variables, foreign investment, inflation, gender empowerment index and corruption perception index in Indonesia. This research uses a quantitative approach with time series data from 2012 - 2021. The results of this study indicate that partially the foreign direct investment variable and the corruption perception index have a positive effect on quality economic growth, while the inflation variable and the gender empowerment index have no effect on quality economic growth. On the other hand, simultaneously the variables of foreign direct investment, inflation, gender empowerment index, and corruption perception index have a significant effect on quality economic growth in Indonesia.